Metastasis of Epidermoid Cervical Carcinoma Cell to The Orbit - Widiastuti Widiastuti; Rachmi Fauziah Rahayu; Djoko Susianto; Rita Budianti; Heru Priyanto; Ambar Moedigdo; Soegiartiningsih Soegiartiningsih (Indonesian Journal of Cancer, 2018)
Orbital metastases of cervical cancer cell are very rare. There is only one case reported in Dr. Moewardi Public Hospital Surakarta between 1999 and 2017. A 45-year-old woman was admitted with the upper right orbital lesion. She had not received a routine gynecologic examination for more than 10 years. She had normal chest X-ray. Abdominal ultrasonography revealed a heteroechoic lesion poor defined edge in cervix utery expands to corpus utery and rectum. Bilateral uropathy obstruction occured. Bone survey demonstrated osteolytic bone metastasis in the right supra orbital bone and a compression fracture of the twelfth thoracal spine. Head and orbital Computed Tomography (CT) scan, which revealed multiple metastatic lesions in the right orbital expanding to extra cranial, was performed. Our diagnosis was cervical cancer FIGO IV-B stage with distant metastasis thus chemoradiation was given. The aim of this report is to give more references regarding this complicated clinical condition.  ABSTRAKKanker serviks metastasis ke orbita sangat jarang terjadi. Hanya satu kasus yang dilaporkan di Rumah Sakit Umum Daerah Dr. Moewardi Surakarta antara tahun 1999 - 2017. Seorang wanita usia 45 tahun dirawat oleh karena lesi di orbita kanan atas sejak 2 bulan yang lalu. Pasien tersebut belum pernah mendapatkan pemeriksaan kandungan rutin selama lebih dari 10 tahun. Foto Chest X Ray normal. Ultrasonografi abdomen tampak lesi heteroekoik batas tak tegas pada serviks uterus meluas ke korpus uterus dan rektum. Terjadi obstruksi uropati kanan dan kiri. Bone survei memperlihatkan gambaran metastasis tipe litik pada tulang supra orbita kanan dan fraktur kompresi pada tulang belakang toraks ke dua belas. Computed Tomography (CT) Kepala dan Orbita memperlihatkan beberapa lesi metastasis pada supra orbita kanan yang meluas ke tulang tengkorak. Diagnosis kami adalah kanker serviks tahap FIGO IV-B dengan metastasis jauh dan diberikan therapi kemoradiasi. Tujuan penulisan ini adalah untuk memberikan lebih banyak referensi data tentang kondisi klinis yang rumit ini.